The jungle book eaudiobook - Kipling, Rudyard (The Jungle Book, 2011)
Children everywhere have read and loved Rudyard Kipling's The Jungle Book—and continue to do so. Here Blackstone offers this collection of moral fables in its entirety. Tales of Mowgli, the boy raised by animals in the exotic jungles of India; Rikki-tikki-tavi, a courageous young mongoose who battles the sinister black cobra Nag; Toomai, the boy who works with elephants; and more will delight listeners both young and old. These classic stories brim with adventure and thrills as the lively characters fend off ferocious tigers and deadly snakes, slip through the jungle to watch elephants dance, and seek refuge from dangerous hunters.